The Potential of Phytomelatonin as a Nutraceutical - Marino B. Arnao; Josefa Hernández-Ruiz (Molecules, 2018)
Phytomelatonin (plant melatonin) is chemically related to the amino acid tryptophan and has many diverse properties. Phytomelatonin is an interesting compound due to its outstanding actions at the cellular and physiological level, especially its protective effect in plants exposed to diverse stress situations, while its vegetable origin offers many opportunities because it is a natural compound. We present an overview of its origin, its action in plants in general (particularly in plant species with high levels of phytomelatonin), and its possibilities for use as a nutraceutical with particular attention paid to the beneficial effects that it may have in human health. The differences between synthetic melatonin and phytomelatonin, according to its origin and purity, are presented. Finally, the current market for phytomelatonin and its limits and potentials are discussed.